Mathematics
KatheleenHolzerland
6

Simplify the fraction -(2x/-xy) completely. a. 2x/-xy b. -2/y c. -2x/xy d. 2/y

+0
(1) Answers
NealPomainville958

[latex]-( \frac{2x}{xy} ) :[/latex] Remove parentheses:  (a) = a [latex]= - \frac{2x}{-xy} [/latex] Apply  the fraction rule : [latex] \frac{a}{-b} = - \frac{a}{b} [/latex] [latex]-( \frac{2x}{xy} )[/latex] Cancel : [latex] \frac{2x}{xy} [/latex] [latex]= -(- \frac{2x}{y} )[/latex] Apply rule : -(-a) = a [latex]= \frac{2}{y} [/latex] Answer D hope this helps!

Add answer